Effects of Dzyaloshinsky-Moriya Interaction on Planar Rotator Model on Triangular Lattice (Communications in Computational Physics, 2020)
The thermodynamic properties and some critical properties of the planar rotator model with chiral Dzyaloshinsky-Moriya (DM) interaction on triangular lattice are analyzed using a hybrid Monte Carlo method. It has been shown that there is a XY-like Berezinskii-Kosterlitz-Thouless (BKT) phase transition in this model. The ground state of this spiral system and the effects of size mismatch are also discussed.